Hubungan Keragaman Pangan, Konsumsi Makan, dan Status Ekonomi Keluarga terhadap Status Gizi Siswa SMP XYZ - Qurbani, Nabila Mahadita; Ayu Mutiara Santanu; Widya Astuti; Isti Kumalasari (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Adolescents are an age group that is in a period of rapid growth and development so that their nutritional needs are relatively high. However, adolescents are also classified as vulnerable to experiencing nutritional problems. Factors that affect the nutritional status of adolescents include the diversity of food available, daily consumption habits, and family socioeconomic conditions. This study aims to analyze the relationship between food diversity, consumption patterns, and family economic status to the nutritional status of junior high school students in the city of Bandung. The study used a cross-sectional design with a quantitative approach, involving 43 students selected through purposive sampling. Data were collected through interviews using the Household Dietary Diversity Score (HDDS) questionnaire to assess family food availability, the Individual Dietary Diversity Score (IDDS) to measure individual food diversity, and a 2x24-hour food recall to determine the adequacy of nutrients. The economic status of the family was determined by the Kuppaswamy scale, while anthropometric measurements were carried out using microtoa and digital scales to determine the height and weight of the respondents. The results showed that economic status was positively significantly related to nutritional status (r = 0.389). This means that the better the family's economic status, the better the nutritional status of adolescents. In contrast, food diversity had a negative relationship with nutritional status (r = -0.030), as well as IDDS scores (r = -0.068). This shows that the variety of food consumed by adolescents is not always directly proportional to nutritional quality, because the factors of amount, portion, and balance of nutrients are also very decisive. In conclusion, the economic status of families influenced by education, type of work, and income level of parents plays an important role in maintaining the nutritional adequacy of adolescents.